Internal efficiency of Public Technical Training Institutions in Bungoma County, Kenya - , Maximilla Wakoli; Kisilu Kitainge (Prof) (IJRDO- Journal of Educational Research, 2019)
No country can develop without quality technical education. However, Technical institutions in developing countries and Africa have been faced with internal efficiency issues for some time. Over the years, TTIs in the region have had to innovate in order to cope with increased competition and diminishing capitation, amongst other objectives, TTIs are to facilitate the running of the parallel programmes for full fee-paying students at both certificate and diploma levels. This paper looks at the internal efficiency of public technical training institutions in Bungoma County, Kenya. The institutions under study were; Sangalo Institute of Science and Technology, Kisiwa, Matili and Musakasa Technical Training Institutes. The research was quantitative in nature. Data was collected through questionnaires and secondary data. The study found out that there has been continuous decline in internal efficiency level in public technical training institutions in Bungoma County. The study recommends that there is need for public TTIs to closely monitor students’ survival from year 1 to year 3 and make a follow up on the reasons that made students not to complete their study on time. Further, transformative resource mobilisation strategies need to be done to ensure internal efficiency levels are raised in public technical training institutions